PENGARUH CITRA MEREK, KUALITAS LAYANAN DAN HARGA TERHADAP PREFERENSI KONSUMEN DALAM MENGGUNAKAN APLIKASI GOJEK - Permana, Septian Davis; Dwiridotjahjono, Jojok (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The emergence of several technological developments in transportation such as Uber, Grab, GoJek provide easy access to certain places and can be reached very quickly with adequate vehicles. This research aims to examine the influence of brand image, service quality and price on consumer preferences in using the Gojek application among students of the Business Administration study program at FISIP UPN "Veteran" East Java. The sample in this study consisted of 90 students in the Business Administration study program FISIP UPN "Veteran" East Java with the characteristics of active students in the Business Administration study program FISIP UPN "Veteran" East Java. The sampling technique in this study used the Purposive Sampling technique because only those taken for students of the Business Administration study program FISIP UPN "Veteran" East Java. Hypothesis testing in this research uses statistical model analysis including validity test, reliability test, classical assumption test, multiple linear regression, F test and t test. The results of this research show that there is a partial influence of the totality of each independent variable on the dependent variable using the t test. Simultaneous testing shows that Brand Image, Service Quality and Price simultaneously have an influence on Consumer Preferences.